"Make no provision for the flesh": recognizing the incarnation in and after Augustine. Issue 1 (2nd January 2018) - Reed, Julia M.
ABSTRACT: This article argues for the importance of the intelligibility of the sexed body to incarnational theology. Building on Mark Jordan's reading of Augustine, I focus on the paradox of the incarnation as both the bodily sign ( signa ) of God and God Godself as the thing that the sign signifies ( res ). Through an analysis of the debates around Leo Steinberg's work on the meaning of Christ's genitals in Renaissance art, I explore the ways in which depicting the incarnation is a paradoxical exercise of depicting God's fully human body. I argue that attention to the paradox of the incarnation as both sign and thing can disrupt ideologies of sexual difference that force bodies to be intelligible as unambiguously sexed, while the question of sexual difference can work within incarnational theology to disturb the equivalence of full humanity and unambiguous maleness.